Culture, institution and diverse approaches to care and care work in East Asia. (July 2018) - Peng, Ito
This article describes two broad approaches to care and care work within a spectrum of approaches that are evident in East Asia: one that accepts care as a core public policy agenda, and tries to leverage it as a potential engine to activate the incipient care economy; and the other, that sees care as strictly private family responsibility, and hence opts to partially underwrite the familial care with a mix of tax and policy incentives through the private market – including creating channels for families to outsource care to foreign migrant care workers. The author uses elder care policies to illustrate ways in which socio-cultural ideas and institutional history shape national policies, and how these policies in turn shape ways in which care is delivered, and care work organized within the family and in the market.